BvBZR1 improves parenchyma cell development and sucrose accumulation in sugar beet (Beta vulgaris L.) taproot - Li, Ningning; Wang, Wei; Guo, Xiaotong; Sun, Yaqing; Li, Guolong; Zhang, Shaoying (Frontiers in Plant Science, 2025)
BRASSINAZOLE-RESISTANT (BZR) transcription factors, key elements of brassinolide (BR) signal transduction, play an important role in regulating plant growth and development. However, little is known about the molecular regulatory mechanism of BZR in sugar beet taproot growth. In this study, BvBZR1 expression was significantly induced by exogenous BR treatment. Transgenic sugar beet overexpressing BvBZR1 exhibited a higher taproot diameter compared with the wild type, mainly due to a significant enhancement in the spacing between cambial rings by increasing the size and layers of parenchyma cells. BvBZR1 regulated the expression of BvCESA6, BvXTH33, BvFAD3, and BvCEL1 and enhanced cell wall metabolism to promote sugar beet taproot growth in parenchyma cells and the development of each cambium ring. In addition, BvBZR1 overexpression significantly increased the accumulation of sucrose and soluble sugars in the taproot, which was attributed to its ability to regulate the expression of BvSPS and BvINV and improve the activity of BvSPS, BvSS-S, BvSS-C, and BvINV enzymes in each cambium ring and parenchyma cell in the sugar beet taproot. These results suggest that BvBZR1 can regulate the expression of genes related to cell wall and sucrose metabolism, improve corresponding enzyme activity, and promote the development of each cambium ring and parenchyma cell, thereby promoting the growth and development of sugar beet taproots.